INNOVATION MANAGEMENT: ESSENCE, TYPES, THE PARTICULAR IMPLEMENTATION - M. Omelchenko (Вестник университета)
The essence and kinds of management innovations are considered in the article. The main factors that hinder their development are as well covered in the article. The sequence of management innovations implementation at the domestic enterprises is suggested and justified.